2002
DOI: 10.1039/b201496n
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic characterisation of 3,4-methylenedioxyamphetamine and 3,4-methylenedioxymethylamphetamine (ecstasy)

Abstract: Combined delta2H, delta13C and delta15N isotopic analysis of MDA and MDMA extracted from seized "ecstasy" tablets provides an isotopic "fingerprint" of the active ingredient allowing individual tablets to be linked to a common batch. Correlating these data with 2H NMR analysis of the extracts has the potential to study both the natural precursor materials and synthetic pathways used in the preparation of MDA and N-substituted homologues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
58
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 24 publications
3
58
0
Order By: Relevance
“…Analysis as described allowed identification of the correct geographic origin of the cocaine in 96% of the cases. In 2002, Carter et al [9] confirmed the 1995 work of Mas et al, [6] which revealed that N isotope analysis presented more discriminating power than C isotope analysis alone. They also went one step further and included H isotope analysis in the study.…”
Section: Irms Of Illicit Drugssupporting
confidence: 73%
“…Analysis as described allowed identification of the correct geographic origin of the cocaine in 96% of the cases. In 2002, Carter et al [9] confirmed the 1995 work of Mas et al, [6] which revealed that N isotope analysis presented more discriminating power than C isotope analysis alone. They also went one step further and included H isotope analysis in the study.…”
Section: Irms Of Illicit Drugssupporting
confidence: 73%
“…Research into forensic applications of this method has thus far focused on narcotic drugs such as heroin, cocaine and MDMA or 'ecstasy'. [16][17][18][19][20] The objective of this study was therefore to determine whether IRMS analysis of paint samples would be a viable forensic tool. In the absence of any published data, there is a need to establish whether isotope data obtained from paint samples would be of sufficient discriminatory power to be of use in the forensic investigations.…”
mentioning
confidence: 99%
“…This sourcing aspect of stable isotopes has also been applied to forensic issues, such as determining the pointof-origin of illicit drugs (11,12) and adulteration of foods and alcoholic beverages (13)(14)(15).…”
mentioning
confidence: 99%